Pelatihan Literasi Investasi Berbasis Syariah bagi Masyarakat Muda Kota Madiun: Mewujudkan Generasi Melek Finansial - La Ode Abdullah; Ridho Muarief; Yopie Diondy Kurniawan (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program aims to enhance Islamic-based investment literacy among the young community of Madiun City. The low level of Islamic financial literacy in Indonesia, which only reached 9.14% (OJK, 2022), indicates the need for educational and practical efforts to increase youth understanding of Sharia-compliant investment principles. The program was implemented through structured Islamic investment literacy training consisting of theoretical sessions, case studies, interactive discussions, and practical simulations. A total of 24 participants, comprising students and young community members, took part in the activity. The pre-test results showed an average score of 44.25, which increased to 78.04 in the post-test, indicating a 33.79% improvement. In addition to cognitive gains, participants also demonstrated positive changes in their attitudes toward ethical and halal investing. This program effectively improved participants’ understanding, skills, and awareness of Islamic investment and contributed to strengthening Islamic financial inclusion at the local level. It is expected that the young generation will become agents of change who promote ethical, responsible, and sustainable financial practices.